‘What is it that’s going on here? And what’s in it for me?’ : How two L2 graduate students experienced spoken interaction - Salter-Dvorak, Hania (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2022)
This paper views classroom interaction as integral to the production of academic writing. It presents a situated account of how two L2 master’s students’ experienced spoken interaction on two different courses, extracted from a small-scale 13-month ethnographic study which drew on Bourdieu’s concept of symbolic capital (1991), and Goffman’s participation framework (1981). Triangulation of classroom observation data with student interviews reveals how interaction is framed by the two research participants’ courses and to what extent interactive events are tied to specific goals related to written assignments. Findings echo existing research that language proficiency, familiarity with norms, and power relations intersect in rendering interaction problematic. I discuss recommendations for enhancing interaction in course design and pedagogy; rather than trans-contextual solutions, constructivist evaluation studies of specific courses are needed which reflect voices of all participants.